Implications of the c.1201C > G (p.Arg401Gly) mutation in FGG gene on fibrinogen stability and function - Lu, Jingyi; Xiang, Zeyi; Ye, Yonglong; Chen, Wei; Tan, Jieyi; Kuang, Bin; Liu, Jun (Frontiers in Medicine, 2025)
Congenital dysfibrinogenemia, a rare coagulation disorder characterized by decreased fibrinogen activity while antigen level is usually normal. We conducted a study on a three-generation family comprising 15 members, among whom three individuals were diagnosed with this condition. This study aimed to elucidate the genetic and structural basis of dysfibrinogenemia in this family. Coagulation assays revealed significantly reduced fibrinogen levels in the proband, his father, and his son, with mild prolongation of PT and TT. Despite normal liver and kidney function, recurrent nosebleeds were reported in the proband and his son. Whole-exome sequencing identified a novel variant (c.1201C > G, p.Arg401Gly) in the FGG gene, confirmed by Sanger sequencing. Structural analysis indicated that the mutation disrupted hydrogen bonding in the FGG protein, compromising its stability and potentially impairing fibrinogen assembly. Scanning electron microscopy of fibrin clots from affected individuals demonstrated a reduced fiber network density compared to healthy controls, further supporting the mutation’s impact on fibrinogen structure. These findings suggest that the p.Arg401Gly mutation in the FGG gene is a likely contributor to the observed dysfibrinogenemia, affecting both protein stability and fibrin network integrity. This study is the first to document the c.1201C > G mutation in the FGG gene, resulting in the substitution of arginine with glycine at the 401st position, consequently impairing fibrinogen function. This discovery holds significant implications for genetic counseling and prenatal genetic diagnosis.